THE IRONY OF ANAEMIA IN INFLAMMATORY BOWEL DISEASE: COMMON BUT UNDERDIAGNOSED AND UNDERTREATED. (8th June 2013) - Tee, W J; Chan, G; Ahmed, Z; Jagun, O; Brady, S; Buckley, M; Sarwar, S; Smyth, C; Farrell, R
Abstract : Introduction: Anaemia is a common systemic complication in inflammatory bowel disease (IBD). Iron deficiency anaemia (IDA) in IBD is often underdiagnosed and undertreated despite its impact on quality of life. There is poor awareness among physicians on the role of oral and intravenous iron replacement in anaemic IBD patients. Oral iron is a low cost treatment but has limited bioavailability and low tolerability. In contrast, intravenous iron appears to be well tolerated and is effective in the treatment of active IBD. Nevertheless, it does incur a strain on healthcare cost, human resources and infrastructure. Aims/Background: To identify the prevalence of IDA in our cohort of IBD patients and to evaluate the adequacy of the treatment of their anaemia. Method: This was a single-centre, retrospective, cross sectional study. All IBD patients in the hospital were recruited. Data was collected by reviewing the IBD database, patient chart and contacting patients directly. IDA patients were identified and their treatment evaluated based on their last hospital admission or outpatient review. IDA was defined as haemoglobin (Hb) <13 g/dL in males or Hb <12 g/dL in females in combination with either microcytosis (MCV<78fl) or transferrin saturation<20%. Active disease was defined as patients with symptomatic disease requiring steroids. Results: Of the 606 IBD patients, only 510 (84.2%) were eventually recruited due to incomplete dataset. There were 273 (53.5%) males and 237 (46.5%) females, median age 43.0±15.6 years. 263 (51.6%) patients had Crohn's disease (CD), 235 (46.1%) had ulcerative colitis(UC) and 11 (2.2%)had indeterminate colitis (IC). Of these, 98/510 (19.2%) had anaemia of which 56/510 (11.0%) were classified as IDA. Of those with IDA, 33 (58.9%) had CD, 21 (37.5%) had UC and 2 (3.6%) had IC, p=0.325. 31 (56.4%) received no oral replacement, 19 (34.5%) received oral iron replacement and 5 (9.1%) received intravenous iron replacement. Those who did not receive any iron replacement had a mean Hb of 11.3 g/dL compared to 10.9 g/dL in those who received iron replacement, p=0.209. In patients with active disease, only 4/18 (22.2%) received intravenous iron replacement. Conclusion: Less than half of our IBD patients with IDA are treated with iron supplementation. Also, only a fifth of those with active disease received intravenous replacement. This is unsatisfactory as oral supplementation in active disease is poorly absorbed. There needs to be more awareness among physicians for the role and route of iron replacement in IBD.